Inclusion of Alaska natives in history/social science curriculum for fifth grade - Panzo, Barbara Ann (CSUSB ScholarWorks, 2000)
This project addresses the need for more authentic multicultural curriculm in the elementary schools within California, specifically concerning Native Americans in Alaska Natives. This projects supports the need to include Alaska Natives in the California History/Social Science curriculum for fifth grade.